[Afisz. Incipit] Państwowy Teatr Wybrzeże Repertuar 8-14.11.1955 r. (Gdańsk : [wydawca nieznany], 1955)
Afisz z repertuarem na 8-14.11.1955 r.
Keywords: Państwowy Teatr Wybrzeże (Gdańsk) -- druki ulotne